Implementasi Biah Lughowiyyah Dalam Meningkatkan Maharah Kalam - Abdul Basith; Yusuf Setiawan (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2022)
The purpose of this research was to determine the implementation of biah lughawiyyah to increase maharah kalam. This research method uses qualitative research. The results of this study indicate that the application of biah lughowiyyah is quite strict, starting from dawn to 23:00 WIB (after evening prayers), in its implementation supervised by language spies appointed by the management. In addition to being required to speak Arabic, mutakhossis is required to memorize 10 words of mufrodat; 5 from isim sentences and 5 from fi'il sentences. In learning, the teacher conveys the material using Arabic. For mutakhossis who violate the obligation to speak Arabic will be sanctioned and for active rooms and mutakhossis who win will receive prizes. The impact of biah lughowiyyah in increasing maharah kalam is that mutakhossis are trained to speak as best they can and are not ashamed to be wrong, a forum for repeating and applying the memorized mufrodat, knowing which sentence structures are right and wrong, sparking enthusiasm for other mutakhossis in speaking Arabic, and remembering and search for unknown mufrodates.